A Monte Carlo Revisiting of N-Methylformamide and Acetone - Almeida, Glauco G. [UNESP]; Cordeiro, Joao M. M. [UNESP] (Soc Brasileira Quimica, 2011)
The pure liquids N-methylformamide and acetone have been revisited via Monte Carlo simulations in the NTP ensemble at 1 atm and 25 degrees C. The molecules are all-atom rigid structures, and the intermolecular potential used is the classical 6-12 Lennard-Jones plus Coulomb. The theoretical g(r)s of both liquids were compared with those obtained from neutron diffraction and empirical potential structure refinement simulations. The results point to the existence of H-bonds driving the N-methylformamide structure, while in acetone the correlations are dipole moment oriented. The structure of the liquid N-methylformamide is mainly guided by a dimer whose molecules are arranged in such a way that the angle between their dipole moments is 73 degrees, while liquid acetone is much less organized and the orientation of the molecules changes from an antiparallel dipolar correlation at short distances to more parallel alignments of the molecular dipole moments for larger distances.
Keywords: Monte Carlo; acetone; N-methylformamide; hydrogen bonds; liquid structure